Pengaruh Media Sosial terhadap Konsumsi Frozen Food di Masa Pandemi COVID-19: The Influence of Social Media on Frozen Food Consumption During the COVID-19 Pandemic - Puji Lestari; Farida Rachmawati (Universitas Airlangga, 2023)
Background: The COVID-19 pandemic has significantly impacted people's lives in Indonesia. The Enforcement of Community Activity Restrictions (PPKM) causes community activities to be online-based (network). This condition impacts the use of social media as a medium of communication and information for each individual. Exposure to social media will also affect changing people's behavior, including consumer behavior. In order to meet consumption needs during a pandemic, frozen food is a more practical and hygienic choice. Objectives: This study aimed to look at the effect of social media on the consumption of frozen food during the COVID-19 Pandemic. Methods: The research design was cross-sectional. The population consisted of students, lecturers, and staff at UIN Walisongo. The total sample was 212 people using a purposive sampling technique. Retrieval data on social media use using a questionnaire and consumption of frozen food using the Food Frequency Questionnaire (FFQ). Results: The results of the Spearman correlation test showed a relationship between social media use and frozen food consumption (p=0.030 and r=-0.149). There is no relationship between mass media use and frozen food consumption (p=0.654 and r=-0.031). Conclusion: There is a significant effect of social media on the consumption of frozen food, and there is no effect of using mass media on the consumption of frozen food.